Disappearing destinations : Climate change and the future challenges for coastal tourism - Jones, Andrew C (CABI Publ, 2015)
This text discusses threats to and consequences of tourism growth, examines research on tourism's impact on coastal zones, reviews current policy iniatives, considers local and national policy options for managing the crisis and makes recommendations aimed at ameliorating projected impacts on coastal tourism infrastructure. Providing a thorough examination of the threats posed to destinations by tourism, this text discusses how popular and fragile destinations such as the Great Barrier Reef could become severely damaged and forced to close to tourists if current tourism trends continue. It is suitable for researchers, policymakers and students in tourism.